Effects of IAA, IBA, NAA, and GA3 on Rooting and Morphological Features of Melissa officinalis L. Stem Cuttings - Hakan Sevik; Kerim Guney (The Scientific World Journal)
This study analyzed the potential of producing Melissa officinalis L. using stem cuttings. Four different hormones (IAA, IBA, NAA, and GA3) were applied to the cuttings, with and without buds, in two doses (1000 mg/L and 5000 mg/L), and after 60 days, 10 morphological characteristics of newly generated plants were detected, and a statistical analysis was carried out. The results of the study show that the cuttings with at least one bud must be used in order to produce M. officinalis using stem cuttings. Even though the auxin group hormones (IAA, IBA, and NAA) do not have an apparent effect on rooting percentage, these hormones were detected to affect the morphological characteristics of the newly generated plants, especially root generation. GA3 application has a considerable effect on stem height.